Pengaruh Beban Klaim Terhadap Jumlah Dana Tabarru (Studi Pada PT. AJS Bumiputera KPS. Medan - Ifrah Allif Bainana; Nur Ahmadi Bi Rahmani; Nurwani Nurwani (Jurnal Riset AKuntansi dan Bisnis, 2022)
The purpose of this study was to analyze the effect of claims expense on tabarru' funds at PT. AJS Bumiputera, KPS Medan in the period 2011-2020. This study uses quantitative data types with an associative approach. The population and sample in this study amounted to 40 with the sampling technique using a saturated sampling technique. The data collection technique of this research was carried out with documentation data. The data analysis technique in this study used descriptive statistical analysis, classical assumption test, simple linear regression test, and hypothesis testing. The results of this study indicate that the Claim Expenses have a significant negative effect on the Amount of Tabarru' Funds, with a coefficient of determination of 0.282 or 28.2%.